The law of search and seizure in Canada - Fontana, James A. (LexisNexis Canada, 2024)
"The Law of Search and Seizure in Canada is the definitive text on all aspects of this intricate and rapidly evolving area of criminal law. Much cited by Canadian courts at all levels, this seminal volume clearly lays out the complex legal framework that governs the issuance, execution and review of search warrants, and the rules limiting warrantless activities by state agents. The book also analyzes the central role of the Charter of Rights in determining the legality of police action and the admissibility of evidence when constitutional protections are breached."-- Provided by publisher.